Dilution of Boundary Layer Cloud Condensation Nucleus Concentrations by Free Tropospheric Entrainment During Marine Cold Air Outbreaks. Issue 11 (6th June 2022) - Tornow, F.; Ackerman, A. S.; Fridlind, A. M.; Cairns, B.; Crosbie, E. C.; Kirschler, S.; Moore, R. H.; Painemal, D.; Robinson, C. E.; Seethala, C.; Shook, M. A.; Voigt, C.; et al.
Abstract: Recent aircraft measurements over the northwest Atlantic enable an investigation of how entrainment from the free troposphere (FT) impacts cloud condensation nucleus (CCN) concentrations in the marine boundary layer (MBL) during cold‐air outbreaks (CAOs), motivated by the role of CCN in mediating transitions from closed to open‐cell regimes. Observations compiled over eight flights indicate predominantly far lesser CCN concentrations in the FT than in the MBL. For one flight, a fetch‐dependent MBL‐mean CCN budget is compiled from estimates of sea‐surface fluxes, entrainment of FT air, and hydrometeor collision‐coalescence, based on in‐situ and remote‐sensing measurements. Results indicate a dominant role of FT entrainment in reducing MBL CCN concentrations, consistent with satellite‐observed trends in droplet number concentration upwind of CAO cloud‐regime transitions over the northwest Atlantic. Relatively scant CCN may widely be associated with FT dry intrusions, and should accelerate cloud‐regime transitions where underlying MBL air is CCN‐rich, thereby reducing regional albedo. Plain Language Summary: Cloud droplets form on a subset of atmospheric particles, referred to as cloud condensation nuclei (CCN). The number concentration of CCN affects the brightness and horizontal extent of clouds. Satellite measurements indicate cloud droplet number concentrations drop off sharply as wintertime marine cold‐air outbreak clouds flow eastward, helping to reduce the brightness and horizontal extent of the clouds. We use aircraft measurements from several flights where cold continental air flowing over the northwest Atlantic to estimate the CCN budget in the near‐surface turbulent air. We show that CCN concentrations in the immediately overlying air, the free troposphere (FT), are usually far less than in the marine boundary layer (MBL). Through additional analysis of one flight, we show that mixing of FT air is the primary factor reducing CCN concentrations in the MBL prior to rain formation, thereby contributing to a reduction in cloud brightness and extent. Key Points: Recent aircraft measurements enable an analysis of cloud condensation nuclei (CCN) during marine cold air outbreaks CCN concentrations are usually less in the free troposphere than in the marine boundary layer over the northwest Atlantic A boundary layer CCN budget indicates a leading role of entrainment dilution up‐wind of cloud‐regime transition